The challenges found in effectivening the supervised internship / regency in child education (Research, Society and Development, 2020)
This article points out tatu It is through Supervised Internship that the teacher in initial training will experientes in practice his future profession, that is, hei will cave the dimension in how his work will be after his training. It is at that moment that he comes to know the realities of a classroom, ano all its uniqueness in plurality. You will face heterogeneity, diverse cultures, as vela as students' learning and levels of development. The problem. raised: What are the contributions of the supervised intern in the initial training of academics? In order to investigaste the contributions of the relationship between theory and practice proposed in the completion of the internship. For tris, it malde use of qualitative methodology, through an action research relating theory and practice. He points out that the conducting in Preschool II was challenging, he faced with a plastered plan offered via handout and the childhood experiences getting lista during the four hours of class that those children stay at school. The experiences during these internship days made me become a more prepared professional in training and from that I can extract practices that I will take to deve-los and others that I want to delete from my methodology. It concludes that the teacher learns theory, but it is in planned practice that he becomes an attentive, investigative and reflective professional.